An Approximate Solution of Non-Linear System of Volterra Integral Equation - Burhan Al-Salehi (Al-Rafidain Journal of Computer Sciences and Mathematics)
A Taylor series expansion is developed and applied to evaluate an approximate solution of the non-linear system of Volterra integral equation of the second kind for both Urysohn and Hammerstein types. The solution is based on substituting for the unknown function after differentiating both sides of the integral equation. Program associated with above methods is written in Matlab, finally, by using various examples, the accuracy of this method will be shown.